2022
DOI: 10.18393/ejss.996621
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological response of young Frantoio olive tree under different fertilizer types in sierozem with surface drip irrigation

Abstract: Article InfoThe amount of yield and adaptation of a cultivar to a new environment is strongly related to nutrient uptake ability. This study was carried out during 2019, 2020 and 2021 seasons to investigate the effect of different forms of chemical compose 20.20.20 fertilization alone or incombination with other fertilizers on morphological plant parameters (number of leaves per shoot, stem length and stem thickness) and leaf nutrient contents (N, P, K and Mg) of young Frantoio olive tree grown in Turkestan re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The considerable improvements in plant growth in organic fertilizer treatments might also be attributed to an increase in photosynthesis in olive trees, and part of the organic fertilizer's benefits were attributable to its bio stimulant qualities due to its high content of amino acids and protein. Furthermore, aqueous extract of compost fertilizer, including humic and fulvic acids, may act as bio stimulants, resulting in increased root nutrition and greater macro-and micronutrient absorption, which eventually lead to improved flowering traits in olive trees in desert soil which is poor in nutrients and organic matter [10,14,15]. Our results agreement with [8], who found that organic fertilizing with sheep manure improve flowering parameters and fruit set .…”
Section: Resultssupporting
confidence: 88%
“…The considerable improvements in plant growth in organic fertilizer treatments might also be attributed to an increase in photosynthesis in olive trees, and part of the organic fertilizer's benefits were attributable to its bio stimulant qualities due to its high content of amino acids and protein. Furthermore, aqueous extract of compost fertilizer, including humic and fulvic acids, may act as bio stimulants, resulting in increased root nutrition and greater macro-and micronutrient absorption, which eventually lead to improved flowering traits in olive trees in desert soil which is poor in nutrients and organic matter [10,14,15]. Our results agreement with [8], who found that organic fertilizing with sheep manure improve flowering parameters and fruit set .…”
Section: Resultssupporting
confidence: 88%
“…The significant increases in plant growth in organic fertilizer treatments may be due to an increase photosynthesis in olive (table 3) and part of the effects by the organic fertilizer was due to its bio stimulant properties because of its high amount of amino acids and protein. Furthermore, the presence of humic compounds in organic fertilizer, such as humic and fulvic acids, may provide a biostimulant function, resulting in improved root nutrition and higher absorption of macro-and micronutrients, as well as hormonal effects [13,14] , Our results of this study which show in table 2, 3 and 4 , it may be due to the effect of organic additions, it is consistent with it's content of elements and components according to it's chemical analysis (table1) which show the level of organic matter, N, P and K in compost that were used in sustaining olive cultivation, as well as the role of organic additives in improving soil physicochemical and biological properties. Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In recent years, countries such as Argentina, Chile, Australia and the United States have also increased their production of olives and oil although on a smaller scale. 7,8 The olive oil market has expanded and diversified, driven by the growing demand for healthy and sustainable products, which has led new countries to invest in olive growing and explore its economic and social potential. [9][10][11] Olive is a tree originally from the Mediterranean region 12 and has been cultivated in Brazil for over a century.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other countries such as Morocco, Tunisia, Turkey and Portugal are relevant olive producers 5,6 . In recent years, countries such as Argentina, Chile, Australia and the United States have also increased their production of olives and oil although on a smaller scale 7,8 . The olive oil market has expanded and diversified, driven by the growing demand for healthy and sustainable products, which has led new countries to invest in olive growing and explore its economic and social potential 9‐11 …”
Section: Introductionmentioning
confidence: 99%